Pharmacokinetic Interaction of Green Rooibos Extract With Atorvastatin and Metformin in Rats - Patel, Oelfah; Muller, Christo J.F.; Joubert, Elizabeth; Rosenkranz, Bernd; Taylor, Malcolm J.C.; Louw, Johan; Awortwe, Charles (Frontiers in Pharmacology, 2019)
An aspalathin-rich green rooibos extract (Afriplex GRT™) has demonstrated anti-diabetic and hypolipidemic properties, while also moderately inhibiting CYP3A4 activity, suggesting a potential for herb-drug interaction. The present study, therefore, evaluated the effects of orally administered GRT on the pharmacokinetics of atorvastatin and metformin in Wistar rats. Wistar rats were orally treated with GRT (50 mg/kg BW), atorvastatin (40 mg/kg BW) or metformin (150 mg/kg BW) alone or 50 mg/kg BW GRT in combination with 40 mg/kg BW atorvastatin or 150 mg/kg BW metformin. Blood samples were collected at 0, 10, 30 min, and 1, 2, 4, 6 and 8 h and plasma samples obtained for LC-MS/MS analyses. Non-compartment and two-compartment pharmacokinetic parameters of atorvastatin and metformin in the presence or absence of GRT were determined by PKSolver version 2.0 software. Membrane transporter proteins, ATP-binding cassette sub-family C member 2 (Abcc2), solute carrier organic anion transporter family, member 1b2 (Slco1b2), ATP-binding cassette, sub-family B (MDR/TAP), member 1A (Abcb1a) and organic cation transporter 1 (Oct1) mRNA expression was determined using real-time PCR expression data normalized to β-actin and hypoxanthine (guanine) phosphoribosyl transferase (HPRT), respectively. Co-administration of GRT with atorvastatin substantially increased the maximum plasma concentration (Cmax) and area of the plasma concentration-time curve (AUC0-8) of atorvastatin by 5.8-fold (p = 0.03) and 5.9-fold (p = 0.02), respectively. GRT had no effect on the plasma levels of metformin. GRT increased Abcc2 expression, whilst the combination of GRT and atorvastatin did not significantly alter the expression of Sclo1b2 or Oct1. Co-administration of GRT with atorvastatin in rats may lead to higher plasma concentrations and therefore to an increase of the exposure to atorvastatin.